Interobserver agreement between emergency clinicians and nurses for Clinical Opiate Withdrawal Scale - Christian A. Tomaszewski; Faith Quenzer; Bryan Corbett; Andrew Lafree; Daniel Lasoff; Jorge Romo; Leslie Mukau (Journal of the American College of Emergency Physicians Open)
Abstract Objectives The Clinical Opiate Withdrawal Scale (COWS) is a validated, commonly used tool to objectively quantify withdrawal symptoms, often in anticipation of treatment with buprenorphine. Our primary aim was to determine the agreement between emergency department (ED) nurses compared with emergency physicians in determining this score in ED patients who presented for opioid withdrawal treatment. Secondarily, we wanted to investigate the safety of buprenorphine induction in the ED setting. Methods Scoring for opioid withdrawal using the COWS was performed by ED clinicians and ED nurses independently on 120 patients. In addition to overall concordance, agreement (weighted kappa) was calculated between the 2 scores by various cutoffs: overall severity, COWS ≥ 5, and the 11 different individual measures. Patient documents also were reviewed for complications that could be possibly linked to buprenorphine induction. Results Our study sample of 120 subjects was 77% Hispanic and 78.3% male. The clinicians assigned a median interquartile range overall COWS score of 6 (2–12), which categorizes as mild withdrawal. Seventy‐eight (65%) subjects met the criteria of withdrawal (≥ 5 COWS) and 69 (58%) received an induction dose of buprenorphine (range 2 mg–24 mg) during the ED visit. No adverse effects or worsening withdrawal were reported. The overall observed concordance, based on severity withdrawal categorization, for all clinician pairs, was 67.5% (81/120) (95% confidence interval [CI], 58.7–75.2%). The weighted kappa for that concordance was 0.55 (95% CI, 0.43–0.67), giving a moderate strength of agreement. When data are dichotomized by COWS score ≥5, concordance was 82.5% (99/120) (95% CI, 74.7%–88.3%) and the weighted kappa was 0.65 (95% CI, 0.51–0.78), indicating substantial agreement. The breakdown by the 11 factors that constitute COWS showed only substantial agreement for pulse measurement. Conclusion The agreement between ED clinicians and nurses for the overall COWS scoring in patients presenting for opioid withdrawal treatment was substantial. COWS scoring by ED nurses may help expedite treatment with buprenorphine on presentation.